Methodical instructions to perform the control work in the discipline "Financial diagnostics in anticrisis management" - Yurieva, Iryna; Tkachenko, M. O. (National Technical University "Kharkiv Polytechnic Institute", 2024)
The study of published scientific works, theoretical concepts, relevant methodological support and empirical analysis of the practice of diagnosing the financial condition of an enterprise in crisis management allowed to identify the range of the most pressing problems that require scientific solution. In-depth research is required on issues related to the definition of the financial and economic mechanism for diagnosing the financial condition of an enterprise in crisis management, methods of diagnosing a financial crisis, analysis of models of financial diagnosis of anti-crisis measures, development of tools for diagnosing the financial condition of an enterprise, in particular, when making decisions in crisis situations in interdependent relations in a crisis condition of an enterprise. The discipline "Diagnostics of the state of the enterprise in crisis management" is one of the subjects, the study of which is due to changes in the economic development of Ukraine. The formation of knowledge and skills of diagnosing the state of the enterprise and crisis management in non-standard crisis and emergency situations is of great importance in the training of modern specialists.
Keywords: methodical instructions; economic activity; finance; anticrisis management; enterprise; SWOT-analysis